(untitled) (Applied Biological Research, 2015)
A nested PCR based prevalence study was done from June, 2011 to May, 2013 to determine the carrier status of Babesia bigemina infection in apparently healthy crossbred cattle from Western semi-arid and Foothill regions of Punjab (India). Of the 278 blood samples collected, an amplicon of 170 bp size was detected in 16.19% animals by nested PCR aa compared to the routine blood smear examination which showed parasitic piroplasms in only 1.80% samples. Regarding various risk factors, statistically non significant variation was observed with respect to zone-wise, sex-wise and age-wise prevalence whereas season-wise disease prevalence showed significant variation (p<0.05).